1996
DOI: 10.1007/bf01781096
|View full text |Cite
|
Sign up to set email alerts
|

Formation and cultivation ofBorrelia burgdorferi spheroplast-L-form variants

Abstract: As clinical persistence of Borrelia burgdorferi in patients with active Lyme borreliosis occurs despite obviously adequate antibiotic therapy, in vitro investigations of morphological variants and atypical forms of B. burgdorferi were undertaken. In an attempt to learn more about the variation of B. burgdorferi and the role of atypical forms in Lyme borreliosis, borreliae isolated from antibiotically treated and untreated patients with the clinical diagnosis of definite and probable Lyme borreliosis and from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 38 publications
1
28
0
2
Order By: Relevance
“…Alleged L-form variant “rigid” SLOs of Borrelia have been described in other papers, from cultured biopsy and synovial fluid samples from Lyme Borreliosis patients [67], [68], in animal skin sample cultures [69] and in control Borrelia cultures subjected to antispirochaetal agents [70], [71]. However, the SLOs in contaminated cultures observed under electron microscopy have been identified by some researchers [69], [72], [73] as large flagella aggregates from the contaminating bacteria, and therefore not indicative of the presence of Borrelia spirochaetes.…”
Section: Potential Reservoirs Of Lyme Borreliosis-causing Borrelia Spmentioning
confidence: 66%
See 1 more Smart Citation
“…Alleged L-form variant “rigid” SLOs of Borrelia have been described in other papers, from cultured biopsy and synovial fluid samples from Lyme Borreliosis patients [67], [68], in animal skin sample cultures [69] and in control Borrelia cultures subjected to antispirochaetal agents [70], [71]. However, the SLOs in contaminated cultures observed under electron microscopy have been identified by some researchers [69], [72], [73] as large flagella aggregates from the contaminating bacteria, and therefore not indicative of the presence of Borrelia spirochaetes.…”
Section: Potential Reservoirs Of Lyme Borreliosis-causing Borrelia Spmentioning
confidence: 66%
“…It is possible that this is what was observed in the cultures conducted by Wills and Barry [66]. However, this does not explain the return of such rigid SLOs to normal, motile spirochaetes after multiple subcultures [66], [67]. SLOs in uncontaminated cultures have been observed by others and can be explained by the flagella passing though filters that block whole bacteria and the flagella then coalesce to form the long SLOs (Doggett, S. pers.…”
Section: Potential Reservoirs Of Lyme Borreliosis-causing Borrelia Spmentioning
confidence: 93%
“…Morphological variants of Bb, some of which are not culturable, are well documented in the medical literature ( Barthold et al , 2010; Hodzic et al , 2014; Kurtti et al , 1987; MacDonald, 2013; MerilĂ€inen et al , 2015; Mursic et al , 1996). These variants may play a role in infection, enabling Bb and other pathogenic spirochetes to evade the immune system ( Döpfer et al , 2012; Menten-Dedoyart et al , 2012; Mursic et al , 1996). Limited Bb growth and non-spiral morphology are thought to be induced by unfavorable environmental conditions ( Brorson et al , 2009), and these features appear to be consistent with our observations.…”
Section: Discussionmentioning
confidence: 99%
“…He notes that these cystic structures, which Bockenstedt et al, observed in their infected animals ( Figure 2 in their study [10]), have been described as a persister mechanism employed by many bacteria, including B. burgdorferi [16][17][18][19][20][21][22][23][24]. The study authors claim that these are not true cysts because they form too fast, appearing in minutes rather than hours or days.…”
Section: Reviewmentioning
confidence: 95%